PERAN PENGEMBANGAN AGROWISATA PANGONAN DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Rhaina Aprilia Madhani; Nonie Afrianty; Badaruddin Nurhab (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the role of Pangonan Agrotourism development in increasing community income from an Islamic economic perspective. The study was conducted at Pangonan Agrotourism, Agung Jaya Village, Air Manjunto District, Mukomuko Regency. The research method used was field research with a descriptive qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation. Research informants consisted of agrotourism managers, community business actors, and village officials selected using a purposive sampling technique. The results of the study indicate that Pangonan Agrotourism development plays a role in increasing community income through the opening of business opportunities, creation of jobs, and increased economic activity of the community around the tourist area. Viewed from an Islamic economic perspective, business activities that have developed in the Pangonan Agrotourism area have generally implemented halal, honest, and mutually beneficial business principles so that they can support community welfare in a sustainable manner